Effect of seed rate and sowing method on foliage production of different genotypes of coriander (Coriandrum sativum L.) (Bangladesh Journal of Agricultural Research, 2013)
A field experiment on coriander (Coriandrum sativum L.) was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during February 2009 to April 2009 to find out the optimum seed rate in relation to sowing methods for maximizing foliage yield of coriander. Four genotypes (CS001, CS002, CS003 and CS008) and three sowing methods (continuous line sowing spaced at 10 cm, 20 cm and broadcast method) and three levels of seed rate (30, 40 and 50 kg/ha) were used as treatment variables.. The result showed that genotype CS003 singly gave the maximum plant height, number of leaves/plant, single plant weight and plant weight/m2 and thus gave the highest foliage yield/ha. Line sowing (10 cm), broadcast method with seed rate @ 50 kg/ha independently produced the maximum foliage weight/m2 and foliage yield/ha. Line sowing (10 cm) with 50 kg/ha seed rate produced the highest foliage yield in case of CS001, CS002 and CS003 genotypes, which was closely followed by broadcast method and the same seed rate. But line sowing (10 cm) as well as broadcast method coupled with 40 kg/ha seed rate gave better foliage yield in genotype CS008. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16970 Bangladesh J. Agril. Res. 38(3): 435-445, September 2013